Analysis correlation of the remaining tooth number and muscle mass in women 45 to 69 years old: a cross-sectional design - Piramida, Delyta; Hamzah, Zahreni; Prijatmoko, Dwi (Padjadjaran Journal of Dentistry, 2024)
ABSTRACT Introduction: Tooth loss is a prevalent condition among older adults. Maintaining at least 20 teeth in the oral cavity is crucial for optimal masticatory function, which in turn is important for adequate nutrient intake, including protein necessary for muscle mass synthesis. This study aimed to analyze the correlation between the number of remaining teeth and muscle mass in women aged 45-69 years, a demographic that typically begins to experience a decrease in muscle mass. Methods: The research used an analytical observational method with a cross-sectional design. Subjects were selected using purposive sampling techniques based on specific inclusion and exclusion criteria, resulting in a sample size of 60 participants. The independent variable was the number of remaining teeth, while the dependent variable was muscle mass. The number of remaining teeth was assessed using a disposable dental kit. Muscle mass was measured with a TanitaⓇ BC-541 digital body composition scale, and height was measured using a microtoise. All participants provided informed consent, and data were recorded on a measurement result sheet. The data were then tabulated and analyzed descriptively and using the Spearman correlation test, with a significance threshold set at 0.000 (p-value <0.05). Results: The correlation coefficient was found to be 0.672, indicating a significantly positive correlation between the number of remaining teeth and muscle mass in women aged 45-69 years. Conclusion: A lower number of remaining teeth is associated with lower muscle mass in women aged 45-69 years.KEYWORDSElderly, tooth loss, muscle mass